IMF Research Bulletin, June 2012. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2012)
The research summaries in the June 2012 issue of the IMF Research Bulletin are "Public Debt in Advanced Economies and Its Spillover Effects on Long-Term Yields" (by C. Emre Alper and Lorenzo Forni) and "Expansionary Fiscal Contractions: The Empirical Evidence" (by Rina Bhattacharya and Sanchita Mukherjee). The Q and A covers "Seven Questions about Income Inequality" (by Laura Feiveson). Also included in this issue are details on visiting scholars at the IMF, a listing of recently published IMF Working Papers and Staff Discussion Notes, as well as information on IMF Economic Review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Factor Income Distribution